A Study on Impact of Working Capital Management on Profitability: A New Dimension from Indian Top Five Cement Companiesâ Perspective - M.Shankar, Azhra Fatima, Sayyad Saadiq Ali, Sai Kishore .V, Kotakonda Balaji Babu (International Journal of Advanced Science and Technology, 2020)
Management of working capital is considered as a âthree facesâ coinâ with each of inventory management, debtors (debtors + receivables) management along with credit suppliers and short-term lenders management. Still there exists a big tragedy between allocation of permanent (fixed) capital and circulating (working) capital. Even from the inception to incredible operations, firms are undergoing the mismatching status of working capital with respect to operational requirements. The present study encompasses the practical guide of WCM to the small cement producing firms in India, as this study has narrated the working capital policy management of largest cement companies in India. The results revealed that, in order to be considered as biggest companies in the Cement world, the selected firms need to strengthen their working capital position to reap more profits. From the analysis, it is clear that there exist a positive relation exist between profitability and components of WCM.